2020
DOI: 10.1017/ipm.2020.61
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbation of OCD symptoms precipitated by media reports of COVID-19

Abstract: The emergence of COVID-19 has recently dominated public discourse given its serious impact on vulnerable patient groups. Advice in relation to reducing risk of contamination has justifiably been circulated widely during the COVID-19 crisis. Contamination fear is a common obsessional theme in patients with obsessive–compulsive disorder (OCD), and there is a need for increased research on how infectious disease epidemics affect patients with OCD. We present the case of a lady in her 30s with a history of well-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 20 publications
3
48
0
1
Order By: Relevance
“…OW patients showed higher rates of Internet checking, mainly for health reassurance or news checking: this could be interpreted as a response to the current global uncertainty and lack of accessibility to non-priority medical services. The impact of media reports on the exacerbation on some OCD features, such as high intolerance of uncertainty along with frequent and excessive online health search have already been described in OCD patients (7,19,20).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…OW patients showed higher rates of Internet checking, mainly for health reassurance or news checking: this could be interpreted as a response to the current global uncertainty and lack of accessibility to non-priority medical services. The impact of media reports on the exacerbation on some OCD features, such as high intolerance of uncertainty along with frequent and excessive online health search have already been described in OCD patients (7,19,20).…”
Section: Discussionmentioning
confidence: 95%
“…To date, the recent literature on mental health consequences of COVID-19 has been mainly focused on the effect of social distancing, self-isolation and quarantining on mental health vulnerability (7). Among the several psycho-social consequences of COVID-19 pandemics, the possible worsening of obsessive-compulsive symptoms has been largely overlooked by health service providers, although empirically-based expert guidance for clinicians has recently been published (8).…”
Section: Introductionmentioning
confidence: 99%
“…It is not therefore surprising that, among published data on mental health impact of COVID-19, different studies reported the frequent onset or worsening of OCD symptoms ( Tian et al., 2020 ). Although so far there are no studies showing an increase in psychiatric emergency admissions for OCD during the period of lockdown in comparison with 2019, some authors highlighted an important increase in obsession and compulsion severity after the onset of the current pandemic ( Abba-Aji et al., 2020 ; French and Lyne, 2020 ; Prestia et al., 2020 ). Specifically, the worsening of OCD symptoms interested especially the fear of contamination (Prestia et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some findings showed that confinement may increase addiction-related habits, including substance use ( Rolland et al., 2020 ). Secondly, contamination fear may be accompanied by anxious and obsessional symptoms, as well as the recurrence of obsessive-compulsive disorder (OCD) symptoms ( Fiorillo and Gorwood, 2020 ; French and Lyne 2020 ). Finally, some studies cited the economic crisis associated with COVID-19 pandemic as potential factor of vulnerability for psychiatric disorders ( Pfefferbaum and North, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Emerging research suggests that the mental health impacts of COVID-19 vary widely, [19][20][21] with sociodemographic factors accounting for some of this variation. For example, studies from the USA 22 23 and other countries [24][25][26][27][28][29][30][31][32][33][34] have shown that women, younger adults, those with lower levels of education and/or income and those with a pre-existing mental or chronic health condition are more vulnerable to the adverse mental health effects of the pandemic. Informal family caregivers may be especially vulnerable to the effects of reduced access to healthcare, social services and resources that are central to the management of their/their loved one's condition, but research on the effects of the pandemic on their emotional well-being has been relatively limited.…”
mentioning
confidence: 99%